PROBLEMS OF CUSTOMER-FOCUSED MANAGEMENT OF THE ORGANIZATION - Y. Voroncova; Y. Goryacheva (Вестник университета)
The elds of admissible use of traditional theoretical approaches to assessment and customer focuse management of the organization and a possibility of their applica-tion in practice are considered. The concept of customer focus is speci ed, and the elds of the most expedient use of the traditional methods allowing to carry out various func-tions of management of customer focus of the organization, are investigated. The main indicators allowing to give an assessment to the level of customer focus of the organiza-tion are allocate, their choice with application of heuristic methods logically is proved